LANGUAGE COMPETENCE AND DEVELOPMENT FROM PLAYGROUND LEARNERS - Ricki Asi Erwindo Siahaan (Sean Institute, 2022)
Development of children’s language acquisition always amazes parents to discuss it details from only communicating by crying , cooing and babbling the very young children go to stages of language development and by the time, they are four months old , children typically acquire hundreds of words , basic grammar but sound to be extraordinary. The objective of study are intended to find out how the children acquire the language competence development of a-three year old-girl. This research uses Qualitative research. The subject of this research is a three years old. Her name is Sere Nauli. She lives in Medan Denai. The subject is preschool in TK.Kemala Bayangkari. She speaks Indonesian language at home every day as her first language. The researcher observes the phenomenon that will happen in the field language competence development of playground learners. This is a kind of an observational single case study. The single case based on naturalistic method where the children are observed in their natural surroundings and their language development and that will be written by the researcher and their utterances will also be recorded in the recorder